(untitled) - Lowe, Doug; Doug Lowe (Hoboken, N.J., 2012)
The demand for Android programming and web apps continues to grow at an unprecedented pace and Java is the preferred language for both. "Java For Dummies Quick Reference" keeps you moving through your coding while you solve a problem, look up a command or syntax, or search for a programming tip. Whether you're a Java newbie or a seasoned user, this fast reference offers you quick access to solutions without requiring that you wade through pages of tutorial material. Leverages the true reference format that is organized with quick answers and solutions so you can read less and do more Offers new elements such as a syntax guide, command guide, special generics and annotation section, and programming tips Boasts a new, compact trim size that easily goes where you go for convenient referencing
Keywords: Java (Computer program language)